Time-Course Transcriptome Analysis of Gingiva-Derived Mesenchymal Stem Cells Reveals That Fusobacterium nucleatum Triggers Oncogene Expression in the Process of Cell Differentiation - Kang, Wenyan; Sun, Tianyong; Tang, Di; Zhou, Jiannan; Feng, Qiang (Frontiers in Cell and Developmental Biology, 2020)
Fusobacterium nucleatum has pathogenic effects on oral squamous cell carcinoma and colon cancer, while the effects of continuously altered gene expression in normal human cells, as induced by persistent exposure to F. nucleatum, remain unclear. In this study, a microarray Significant Profiles (maSigPro) analysis was used to obtain the transcriptome profile of gingiva-derived mesenchymal stem cells (GMSCs) stimulated by F. nucleatum for 3, 7, 14, and 21 day, and the results revealed 790 (nine clusters) differentially expressed genes (DEGs), which were significantly enriched in cell adherens junctions and cancer-related pathways. On the basis of a short time-series expression miner (STEM) analysis, all the expressed genes in the GMSCs were grouped into 50 clusters according to dynamic gene expression patterns, and the expression levels of three gene clusters in the F. nucleatum-treated GMSCs were significantly different than the predicted values. Among the 790 DEGs, 50 tumor-associated genes (TAGs; such as L3MBTL4, CD163, CCCND2, CADM1, BCL7A, and IGF1) and five core dynamic DEGs (PLCG2, CHI3L2, L3MBTL4, SH2D2A, and NLRP3) were identified during F. nucleatum stimulation. Results from a GeneMANIA database analysis showed that PLCG2, CHI3L2, SH2D2A, and NLRP3 and 20 other proteins formed a complex network of which 12 genes were enriched in cancer-related pathways. Based on the five core dynamic DEGs, the related microRNAs (miRNAs) and transcription factors (TFs) were obtained from public resources, and an integrated network composed of the related TFs, miRNAs, and mRNAs was constructed. The results indicated that these genes were regulated by several miRNAs, such as miR-372-3p, miR-603, and miR-495-3p, and several TFs, including CREB3, GATA2, and SOX4. Our study suggests that long-term stimulation by F. nucleatum may trigger the expression of cancer-related genes in normal gingiva-derived stem cells.